Предмет: Алгебра,
автор: Chabak2306
1)) 5y - (6y + x) - (x - 6y) = 5y - 2x 2)) 3x =1,2(x-7)-1,8(3-x)+13,8 3)) 3(8x - 4) + 6x = 2(15x - 6) 5)) 16 - 3(2 - 3y) + y = 10(y + 1) 6)) 5x - 2(3x - 1) = 2 - x 4) 10 = 2(y - 1) - 2y + 12 ПОМОГИТЕ ПОЖАЛУЙСТА, ЭТО ОЧЕНЬ СРОЧНО ДАМ ВСЁ БАЛЫ
Ответы
Автор ответа:
1
1). 5y - (6y + x) - (x - 6y) = 5y - 2x
5y - 6y - x - x + 6y = 5y - 2x
-2x + 5y = 5y - 2x
-2x + 2x = 5y - 5y
0 = 0
2). 3x = 1,2 (x - 7) - 1,8 (3 - x) + 13,8
3x = 1,2x - 8,4 - 5,4 + 1,8x + 13,8
3x - 1,2x - 1,8x = 0
0 = 0
3). 3 (8x - 4) + 6x = 2 (15x - 6)
24x - 12 + 6x = 30x - 12
30x - 30x = - 12 + 12
0 = 0
5). 16 - 3( 2 - 3y) + y = 10 (y + 1)
16 - 6 + 9y + y = 10y + 10
10y - 10y = 10 - 10
0 = 0
6). 5x - 2(3x - 1) = 2 - x
5x - 6x + 2 = 2 - x
- x + x = 2 - 2
0 = 0
4). 10 = 2 (y - 1) - 2y + 12
10 = 2y - 2 - 2y + 12
10 - 10 = 0
0 = 0
Похожие вопросы
Предмет: Английский язык,
автор: vaallxzz5
Предмет: Математика,
автор: vvk822377
Предмет: История,
автор: cutekittyhelloo
Предмет: Английский язык,
автор: pops4148